Some Relations between Twisted (h,q)-Euler Numbers with Weight α and q-Bernstein Polynomials with Weight α - N. S. Jung; H. Y. Lee; C. S. Ryoo (Discrete Dynamics in Nature and Society)
By using fermionic p-adic q-integral on ℤp, we give some interesting relationship between the twisted (h, q)-Euler numbers with weight α and the q-Bernstein polynomials.